1988
DOI: 10.1002/glia.440010206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane of cultured oligodendrocytes: III. Relatedness to myelin

Abstract: We have compared highly purified fractions of oligodendrocyte plasma membrane to myelin by one- and two dimensional gel electrophoresis and found them to be distinct. The major myelin proteins--proteolipid protein (PLP), DM-20, and myelin basic protein (MBP), which dominate the sodium dodecyl sulfate polyacrylamide gel electrophoresis pattern of myelin--were minor components of the plasmalemma. However, 2',3', cyclic nucleotide phosphodiesterase (CNPase) and myelin-associated glycoprotein (MAG) were represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…A colocalization between MBP and the microtubule protein tubulin has also been reported (48). In a comparative study of the protein composition of highly purified fractions of OLG plasmalemma and myelin by two-dimensional gel electrophoresis, Szuchet et al (49) showed that both membranes had actin and a-and f3-tubulins. However, there were significant differences in their contents: OLG plasmalemma was enriched in actin relative to the tubulins; the opposite was the case for myelin.…”
Section: Discussionmentioning
confidence: 84%
“…A colocalization between MBP and the microtubule protein tubulin has also been reported (48). In a comparative study of the protein composition of highly purified fractions of OLG plasmalemma and myelin by two-dimensional gel electrophoresis, Szuchet et al (49) showed that both membranes had actin and a-and f3-tubulins. However, there were significant differences in their contents: OLG plasmalemma was enriched in actin relative to the tubulins; the opposite was the case for myelin.…”
Section: Discussionmentioning
confidence: 84%
“…Given that OLG plasma membrane and myelin are compositionally distinct beyond the major proteins (Jahn et al, 2009;Szuchet et al, 1988;Vanrobaeys et al, 2005), questions concerning myelin synthesis, transport and deposition are highly pertinent and, yet, remain largely unanswered. We have addressed these topics using transmission electron microscopy (TEM), immuno-EM and threedimensional electron tomography (3D-ET) on an in vitro model consisting of pure cultures of OLGs and on embryonic (E) avian optic nerve at stages E12, E15, E17 and E21.…”
Section: Introductionmentioning
confidence: 99%
“…Immunocytochemical examination of sections of CNS tissue demonstrated that in vivo it is present in the periaxonal membranes and cytoplasm of oligodendrocytes (Sternberger et al, 1979;Trapp et al, 1989). It has also been detected immunocytochemically in cultured rat (Dubois-Dalcq et al, 1986) and mouse (Poltorak et al, 1987) oligodendrocytes and by Western blotting in cultured porcine (Gebicke-Harter et al, 1984) and ovine (Yim et al, 1986;Szuchet et al, 1988) oligodendrocytes. However, biochemical investigation of MAG in cultured oligodendrocytes is limited so far to cells from developing rat brain where the presence of mRNA for both isoforms (Tropak et al, 1988) and its phosphorylation (Bambrick and Braun, 1991) have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%